Obstacles to Women’s Rights to Education: The Taliban Regime and Its Policies on Women’s Education in Afghanistan - Mir Hussain Amiri (Centre for Asian Social Science Research (CASSR), Faculty of Social and Political Sciences, UIN Sunan Gunung Djati Bandung, 2023)
In Afghanistan, significant progress has been made in education, particularly after the formation of the interim government. However, challenges persist, including the gender gap in education. While strides have been made, girls' participation in schools and universities remains low, especially in rural areas due to cultural and traditional constraints. The Taliban's rule in the past has caused significant damage to Afghanistan's education system, particularly for women and girls. Despite promises of moderation, the recent return of the Taliban has not resulted in improved access to education for girls, further exacerbating the challenges faced by Afghan youth. Education is an indispensable force for societal advancement, shaping individuals and cultures. In the case of Afghanistan, progress has been made, but significant obstacles, including gender disparities and the impact of Taliban rule, remain to be addressed to ensure equitable access to education and empower Afghan youth.